Akselerasi Pengembangan Pariwisata Indonesia yang Berkelanjutan - Sayuti, Memet Achmad (Politeknik Pariwisata NHI Bandung, 2018)
The growth of world tourism industry was indicated by increasing 4,7% in 2014 compared to 2013, reach over 1.138 billion tourist. Tourism fundamentally generate economic activity in destination all around the world. Sustainability still become main issue in tourism development, pushed to balance between mass tourism and alternative tourism. This happens also in Indonesia, when